Saxitoxinas GTX 2,3, dc-GTX 2,3 EC 1,2 em água de abastecimento público: estabilidade e validação de método analítico - Mileo, Marianna Correia Aragão (2014)
The water quality of reservoirs for water supply has been compromised due to eutrophication. Eutrophication favors the proliferation of cyanobacteria, and therefore cyanotoxins that can be produced and released at any stage of cell growth of cyanobacteria. When these are in excess toxins in reservoirs and fountains, represent a hazard to public health and may cause poisoning in humans and animals. Due to several published reports that indicate fatal poisoning caused by cyanotoxins in Brazil and the world, the Brazilian health authorities have given more attention to the issue of intoxication by cyanotoxins, culminating with the inclusion of concentration limits for microcystin and saxitoxin to the concierge potability of the Ministry of Health 2914/2011. The methods described in the literature for the determination of saxitoxins, no reports of validation of the method for analyzing Goniautoxina 2.3 (GTX 2.3) were found Decarbamoil Goniautoxina 2,3-(2,3 dc-GTX) and N -sulfocarbamoil-Goniautoxina 2.3 (1.2 C) in water samples from reservoirs for public water supply. Within this context, this work aims to validate analytical methodology to identify and quantify 2.3 GTX, GTX-dc 2.3 and 1.2 C, using high-efficiency liquid chromatography with fluorescence detection (HPLC-FLD). Validation was performed in accordance with Resolution 889/2003 of ANVISA. The toxin C 1.2 has not remained stable and deteriorated rapidly, preventing its detection and completion of validation. For the 2.3 GTX and GTX-2.3 dc toxins, selectivity and linearity shown to be satisfactory. The values ​​obtained for the precision, accuracy, limits of detection and quantification of the instrument and the method presented is suitable values ​​allowed by Brazilian law, with the exception of accuracy in small concentrations. The method proved to be robust as the analysis of peak area and show sensitivity to temperature variation and the analysis of the retention time. From the final analysis of the results of each parameter, the method proved to be valid for the determination of 2.3 GTX and GTX-dc 2.3.